2006
DOI: 10.1103/physrevd.73.054005
|View full text |Cite
|
Sign up to set email alerts
|

Model-independent study of magnetic dipole transitions in quarkonium

Abstract: We study magnetic dipole (M1) transitions between two quarkonia in the framework of nonrelativistic effective field theories of QCD. Relativistic corrections of relative order v 2 are investigated in a systematic fashion. Nonperturbative corrections due to color-octet effects are considered for the first time and shown to vanish at relative order v 2 . Exact, all order expressions for the relevant 1=m and 1=m 2 magnetic operators are derived. The results allow us to scrutinize several potential model claims. I… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
239
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(260 citation statements)
references
References 45 publications
19
239
2
Order By: Relevance
“…non-relativistic QCD (pNRQCD) [12], lead to a very good agreement with lattice QCD results [13]. Therefore, as of today, the theoretical estimate of Γ(J/ψ → η c γ) is very solid.…”
Section: Jhep05(2015)014supporting
confidence: 55%
See 1 more Smart Citation
“…non-relativistic QCD (pNRQCD) [12], lead to a very good agreement with lattice QCD results [13]. Therefore, as of today, the theoretical estimate of Γ(J/ψ → η c γ) is very solid.…”
Section: Jhep05(2015)014supporting
confidence: 55%
“…Quark model predictions of the hadronic matrix element governing this decay are difficult to control because the leading term vanish due to orthogonality of the meson wave functions and the relativistic corrections are highly sensitive to the form of the used potential. Phenomenology of this decay mode has not been considered in the effective theory approach [12]. It is often assumed to be similar in size to Γ(ψ(2S) → η c γ) which has been measured and found to be small.…”
Section: Jhep05(2015)014mentioning
confidence: 99%
“…The effective theory approach of ref. [47] and the QCD sum rule analyses [48,49] succeeded at getting lower value for the decay rate of this decay, but with large uncertainties. Note that the dispersive (model independent) approach of ref.…”
Section: Jhep01(2013)028mentioning
confidence: 99%
“…Systematic investigation of the M1 transitions in the framework of nonrelativistic effective field of QCD has been reported in Ref. [30], where relativistic corrections of relative order v 2 are included. For J/ψ → γη c the authors found Γ J/ψ→γηc = (1.5 ± 1.0) keV, which is in a good agreement with the data, but with quite large estimated uncertainties from higher-order relativistic corrections.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical studies of the heavy quarkonium M1 transitions with relativistic corrections are various in the literature [24,25,26,27,28,29,30,31]. Relativistic quark model calculations show that a proper choice of the Lorentz structure of the quark-antiquark interaction in a meson is crucial for explaining the J/ψ → γη c data [27].…”
Section: Introductionmentioning
confidence: 99%